Frontispiece: Excited‐State Dynamics of Non‐Luminescent and Luminescent π‐Radicals. Issue 5 (29th January 2020) - Teki, Yoshio
Abstract : Excited‐state dynamics of non‐luminescent and luminescent π‐radicals and related spin systems are emerging topics both in fundamental science and related technological applications. This Minireview, by Y. Teki on page 980 ff., covers effective generation of high‐spin photoexcited states and control of the excited‐state dynamics using non‐luminescent π‐radicals, unique excited‐state dynamics of luminescent π‐radicals, and applications utilizing excited‐state dynamics of π‐radicals.